47th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2011
DOI: 10.2514/6.2011-5649
|View full text |Cite
|
Sign up to set email alerts
|

Biglobal Instability of the Bidirectional Vortex. Part 2: Complex Lamellar and Beltramian Motions

Abstract: Having established the framework for biglobal hydrodynamic instability of an incompressible mean flowfield in Part 1 of this two-paper series, the present focus is turned towards applications. To this end, the instability of the bidirectional vortex motion is analyzed using the biglobal approach. Three distinct mean flow profiles are considered, specifically, the complex-lamellar, linear, and nonlinear Beltramian motions. Their spectral characteristics and eigensolutions are computed and compared to one anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…His approach was further extended to accommodate arbitrary endwall injection by Akiki and Majdalani [73,74]. As for compressibility effects and stability of cyclonic motions, these were addressed in a series of studies by Maicke and Majdalani [75][76][77] and, for the stability assessment, by Batterson and Majdalani [78,79]. The last set supported the notion that flow stability could be continuously enhanced with successive increases in the swirl velocity.…”
Section: Introductionmentioning
confidence: 93%
“…His approach was further extended to accommodate arbitrary endwall injection by Akiki and Majdalani [73,74]. As for compressibility effects and stability of cyclonic motions, these were addressed in a series of studies by Maicke and Majdalani [75][76][77] and, for the stability assessment, by Batterson and Majdalani [78,79]. The last set supported the notion that flow stability could be continuously enhanced with successive increases in the swirl velocity.…”
Section: Introductionmentioning
confidence: 93%
“…The method has been proven to be unconditionally stable and, hence, effective at solving stiff, oscillatory ODEs and PDEs. Batterson and Majdalani 45,46 and Batterson 16 have successfully employed this technique to study biglobal instability and vortical motion by solving systems of PDEs that arise in the context of hydrodynamic and vorticoacoustic waves in simulated solid and liquid rockets. In these and many such studies, Chebyshev polynomial collocation has shown distinct advantages in the…”
Section: Third Gst Correction For the Type II Solutionmentioning
confidence: 99%
“…Following previous works, 26,27,35 Chebyshev collocation is selected over other discretization methods due to its simplicity and straightforward implementation. We define a discrete Chebyshev polynomial of order N as …”
Section: Chebyshev Discretizationmentioning
confidence: 99%
“…24 In the latter, direct numerical simulations of cylindrically-perforated solid rocket motor grains are shown to spectacularly agree with biglobal stability predictions of the chamber's unsteady motion when properly augmented by the vorticoacoustic wave contribution, formulated by Majdalani and Van Moorhem. 25 In liquid rocket flowfield stability, the first noteworthy investigation may be attributed to Batterson and Majdalani 26,27 and their biglobal stability analysis of the bidirectional vortex motion; the corresponding problem arises in the context of the so-called Vortex Combustion Cold Wall Chamber (VCCWC) by Chiaverini et al [28][29][30][31] This two-part series provides the detailed analytical derivation, numerical discretization steps, and spectral collocation tools needed to handle the complete set of partial differential equations that emerge in a problem where the parallel flow assumption proves to be unsuitable. The Batterson-Majdalani series also illustrates the practical applications of biglobal stability to incompressible helical profiles.…”
Section: Introductionmentioning
confidence: 98%